EXPLORATION OF GENETIC VARIATIONS IN KETEKI JOHA RICE (ORYZA SATIVA L.) THROUGH RNA-SEQUENCING (CAHIERS MAGELLANES-NS, 2024)
The study investigates genetic variations, particularly single nucleotide polymorphisms (SNPs) and insertions/deletions (InDels), in the Keteki Joha rice variety using RNA-sequencing data. By pre-processing raw reads, mapping them to the Japonica genome, and applying variant calling tools, a comprehensive analysis of the genetic diversity within Keteki Joha rice was performed. The study identified a total of 342,641.3 variants, with SNPs constituting 68% and InDels 32%. Chromosome 1 exhibited the highest number of variants, while chromosome 9 had the least. The research also examined the functional impact of these variants, revealing significant effects on gene structure and protein function. This exploration of genetic diversity in Keteki Joha provides insights into its adaptability and potential for breeding programs, emphasizing the importance of conserving this unique rice variety.